PATIENT SATISFACTION WITH KNEE ARTHROSCOPY UNDER LOCAL ANESTHESIA AND SEDATION - Andonovski, Аlan; Foteva, Marta; Andonovska, Biljana; Popovska, Danica (Department of Anaesthesia and Reanimation, Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, R.N. Macedonia, 2024)
Introduction: Knee arthroscopy can be performed under general, regional (spinal or epidural) or local anesthesia with different patients’ satisfaction after surgery. Purpose: The aim of our study was to evaluate the level of satisfaction in patients after knee arthroscopy under local anesthesia. Patients and methods: The study included 52 patients where knee arthroscopy under local anesthesia was performed at the University Clinic for Orthopedic Surgery in Skopje, North Macedonia in the period from February 2021 to February 2022. The study did not include patients with allergy to the used drugs, infection at the portal sites of injection, any previous surgery to the knee, patients with chronic extensive synovitis or gross deformity of the knee (severe varus or valgus knee), as well as those with psychological problems, severe systemic disease, consumption of analgesics or non-steroidal anti-inflammatory drugs within 24 h of surgery, bleeding diathesis or coagulopathy. Evaluation of patients’ satisfaction after surgery was done one to three months later by determining the level of satisfaction, pain during surgery, anesthesia-related postoperative complications and preference of this anesthetic technique in the future. Results: The majority of patients were either very satisfied (84.6%) or satisfied (9.6%) with local anesthesia for knee arthroscopy. Only 1.9% of them were not satisfied at all. Most of the patients reported no pain (80.8%) or mild pain (11.5%) during knee arthroscopy under local anesthesia. Only 1.9% of patients complained of strong or very strong pain during arthroscopy. Of all patients, 51 (98%) had no anesthesia-related problems after surgery except one patient who had redness, pain, swelling and blisters formation on the portal where local anesthetic and adrenaline were previously injected. Most of the patients (96%) reported that they would choose local anesthesia for knee arthroscopy again. Conclusion: Our study showed that most patients had no pain, were very satisfied and would choose local anesthesia for knee arthroscopy again.
Keywords: knee arthroscopy; local anesthesia; patients’ satisfaction